Organizational learning orientation and sustainable competitive advantage: towards more accountable government-linked companies / Nur Nadiah Zulkarnain ...[et al.] - Zulkarnain, Nur Nadiah; Nik Abdullah, Nik Herda; Said, Jamaliah; Alam, Md. Mahmudul (Penerbit UiTM (UiTM Press), 2016)
Government-linked companies (GLCs) are organizations in which the government owns at least 20% of the issued and paid-up capital. GLCs are expected to be actively involved in learning orientation to reflect a high level of accountability to taxpayers' money. This study assessed the status of the current level of organisational learning orientation among GLCs in Malaysia. Primary data were collected by conducting a questionnaire survey on 134 executives and managers of GLCs in Malaysia. The data included opinions on 10 factors of organisational learning practices. A fivepoint Likert scale was used for evaluation. The data were analysed through descriptive statistics. Furthermore, the reliability of the data was tested with Cronbach's alpha test, and data validity was tested by conducting a normality test and evaluating skewness and kurtosis. Data consistency was tested through a factor analysis. A total of 74.6% of the respondents stated that they focus on the factors of organisational learning. Federal-owned GLCs place more emphasis on organisational learning than state-owned GLCs. This study recommends that the practices of organisational learning of GLCs in Malaysia be improved by emphasising that employee learning is an investment rather than an expense. Employees should view themselves as partners in charting the direction of the organisation and should not be afraid to reflect critically on the shared assumptions about how the organization is managed. Unsuccessful organizational endeavours must be analysed, and the lessons learned should be communicated widely among employees.